TATA KELOLA ANGGARAN DESA YANG BERSUMBER APBN DALAM RANGKA MEWUJUDKAN PEMBANGUNAN MASYARAKAT PINGGIRAN BERBASIS PEMERATAAN PEMBANGUNAN PEDESAAN DALAM PERSPEKTIF NAWA CITA (STUDI KASUS DI WILAYAH CIAYUMAJAKUNING) - Sugianto, Sugianto; Leliya, Leliya; Ubaidillah, Ubaidillah (Universitas Wiralodra, 2018)
Rural development in an integral part of regional development and national development as an effort to improve the quality of community’s life. The implementation of this rural development program is very important in the context of national development because rural areas occupy the largest portion in the entire country. The purpose of this study was to find out the village budget management sourced from the state budget in order to realize rural community development based on rural development in the perspective of Nawa Cita and the role of the village government in running the Nawa Cita program on peripheral community development on village government budget management based on people’s interest in order to realize equitable development. This study used a qualitative approach in order to investigate and understand the phenomena such as what happens, why it happens, and how it happens while understanding a social situation, events, and interaction roles. Data collection was carried out by conducting interview with the Head of BPMPD Department of Cirebon Regency, the Head of BPMPD Department of Kuningan Regency, the Head of BPMPD Department of Majalengka Regency and the Head of BPMPD Department of Indramayu Regency and all village heads in Cirebon, Indramayu, Majalengka, and Kuningan Regions. As well as the data were obtained from the documents in regency, disctrict, and village. The result of this study showed that village as the frontline of the development has strategic role in the success of the Nawa Cita Program. The village budget management is based on the principle of transparency, accountability, participatory, efficient, effective, orderly and budgetary discipline by paying attention to the justice principles, propriety and benefits for the village community. The implementation of activities in the APBD is carried out by the implementing team consisting of the elements from village apparatus and community institutions and supervised by the BPD, at the end of each fiscal year the Village Head has the obligation to submit a village government management report (LPPD) to the regional head through sub-district head and submit information to the LPPD to the BPD.